(untitled) (Medico Legal Update, 2020)
Ethics is the understanding and the ability to differentiate right from wrong in human behavior. Dental ethics denotes moral duties and obligations of a dental practitioner towards their patients, fellow colleagues, and the society at large. An ethical practice among dentists ensure good patient care in concurrence with their treatment needs. Ethical principles and codes introduced by regulatory bodies benefit the patient, avoid harm, and respect patient’s preferences. Ethical dilemmas are faced by orthodontists during orthodontic interventions, even though important human values may be at stake during the course of treatment. The code of ethics in dentistry warrants an orthodontist to act in the best interest of their patients regardless of their financial status, even putting themselves at jeopardy if need be. This article thus focuses on the morals and ethics that should be abided by an orthodontist in order to deliver the best possible care to their patients.